PKM Workshop And Graphic Design Photography Exhibition For Students - Yodiansyah, Hefri; Jummaulana, Harry; Salim, Ermairel; Sartika, Sartika (Pasundan Community Service Development, 2025)
The rapid development of digital technology has encouraged the importance of mastering visual communication skills among the younger generation, especially students. Photography and graphic design are now strategic media in conveying messages, building images, and expressing ideas creatively and communicatively. In response to this need, this Community Service (PkM) activity was held with the main aim of improving student competence in the fields of photography and graphic design through the implementation of workshops and exhibitions of visual works. This activity involved students from UIN Suska Riau and Universitas Islam Riau, and presented speakers from professional circles to provide technical training related to photography techniques, vector-based graphic design principles, color utilization, visual composition, and the use of design software such as Adobe Photoshop and Canva. In addition to training, this activity also presented an exhibition of student work as a form of appreciation and space for public expression of the participants' creativity. Evaluation of the results of the activity showed that 92% of participants experienced significant improvements in technical skills and self-confidence. Some participants even started building digital portfolios and expanding networks with creative communities online. This program not only has an impact on improving individual abilities, but also strengthens the synergy between the academic world and the creative industry in creating an applicable, collaborative, and sustainable learning ecosystem. Thus, this activity is expected to become a model for student development based on practical and actual skills in the creative economy era.